Avoiding False-Positive SARS-CoV-2 Rapid Antigen Test Results with Point-of-Care Molecular Testing on Residual Test Buffer - Jason J. LeBlanc; Gregory R. McCracken; Barbara Goodall; Todd F. Hatchette; Lisa Barrett; John Ross; Ross J. Davidson; Glenn Patriquin (Microbiology Spectrum, 2022)
ABSTRACT Antigen-based rapid diagnostic tests (Ag-RDTs) have been widely used for the detection of SARS-CoV-2 during the coronavirus disease 2019 (COVID-19) pandemic. In settings of low disease prevalence, such as asymptomatic community testing, national guidelines recommend confirmation of positive Ag-RDT results with a nucleic acid amplification test (NAAT). This often requires patients to be recalled for repeat specimen recollection and subsequent testing in reference laboratories. This project assessed the use of a point-of-care molecular NAAT for SARS-CoV-2 detection (i.e., ID NOW), which was performed on-site at a volunteer-led asymptomatic community testing site on the residual test buffer (RTB) from positive Ag-RDTs. The ID NOW NAAT assay was performed on RTB from two Ag-RDTs: the Abbott Panbio and BTNX Rapid Response assays. Results of ID NOW were compared to real-time RT-PCR at a reference laboratory. Along with investigations into the clinical performance of ID NOW on RTB, analytical specificity was assessed with a panel of various respiratory organisms. Of the Ag-RDTs results evaluated, all 354 Ag-RDTs results characterized as true positives by RT-PCR were accurately identified with ID NOW testing of RTB. No SARS-CoV-2 detections by ID NOW were observed from 10 specimens characterized as false-positive Ag-RDTs, or from contrived specimens with various respiratory organisms. The use of on-site molecular testing on RTB provides a suitable option for rapid confirmatory testing of positive Ag-RDTs, thereby obviating the need for specimen recollection for molecular testing at local reference laboratories. IMPORTANCE During the COVID-19 pandemic, rapid antigen tests have been widely used for the detection of SARS-CoV-2. These simple devices allow rapid test results. However, false-positive results may occur. As such, individuals with positive rapid tests often must return to testing centers to have a second swab collected, which is then transported to a specialized laboratory for confirmation using molecular tests. As an alternative to requiring a repeat visit and a prolonged turn-around time for result confirmation, this project evaluated whether the leftover material from rapid antigen tests could be confirmed directly on a portable point-of-care molecular instrument. Using this approach, molecular confirmation of positive antigen tests could be performed in less than 15 min, and the results were equivalent to laboratory-based confirmation. This procedure eliminates the need for individuals to return to testing centers following a positive rapid antigen test and ensures accurate antigen test results through on-site confirmation.